**Answer:**

C. Incomplete sentences

**Step-by-step explanation:**

**Answer:**

B

**Step-by-step explanation:**

The answer is B because in order for the square root of a number to be equal to another number, the answer squared should be the number under the square root.

the problem would be set up as 6+(7*x)=41

first u take off the number 6 by subtracting it from itself to cancel it out then u do the same to the number 41

7x =41 now u need to cancel out the number 7 attatched to the x so u divikde it by itself and then do the same to the other side so 41 divided by 7 =5.9

so x =5.9

Any improper fraction would work for this case since they are all greater than 1. For instance 3/2 * 2 would be equal to 3 which is greater than 2.

**Answer:**

0.1875

**Step-by-step explanation:**

σM=σ/√N

=8/√7500

=8/86.608

=0.092

Z=(x-μ)/σ/√N

=(25.5-36)/8/√7500

=-10.5/0.0092=-1141.304

Z score = -1.3125

=(27-36)/8/√7500
=

=9/0.0092=978.261

Z score= -1.125

-1.125-(-1.3125)=-1.125+1.3125)= 0.1875

The probability that the sample mean will be between 25.5 and 27 years

P(between 25.5 and 27) = 0.1875